KAJIAN FAKTORâFAKTOR YANG DIDUGA BERASOSIASI DENGAN RESIDU DELTAMETHRIN PADA AYAM BROILER DI KECAMATAN BERBAH DAN KALASAN KABUPATEN SLEMAN - , FIRMAN AKBAR ROMADHON; , drh. R. Gagak Donny Satria, M.P., M.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Broiler is a type of chicken that is highly effective in meat production. Well planned farm management can ensure that the maximum meat production ofbroilers. The chicken farm system that is commonly used is litter system. Pest control is an important aspect of animal health management and biosecurity on farms. The use of pesticides is one of the methods in pest controlling. As Indonesia is mainly depending on the farming sector, pesticides are frequently used in this country. The overuse of pesticides can pollute the environment. Deltamethrin as a broad-spectrum pyrethroid, is the currently most widely used insecticide in Indonesia because of its lethal effect on insects. The overuse of chemical-based pesticides can be left in the cycle and can be either directly or indirectly consumed by humans. This thesis aimed to understand the factors associated with exposure ofdeltamethrin residual in broilers atBerbahand Kalasan districts, Sleman. Samples of blood, liver, and muscle from the left drumstick were taken from chickens from 15 farms in Berbah and Kalasan districts, Sleman.Detecting of pesticide residue was conducted at the Pharmacology Laboratory, Faculty of Veterinary Medicine, Gadjah Mada University. Interviews and questionnaires were conducted to gather information on farming management practices. Data analysis by using Chi-square test and relative risk analysis was to determine management processes which had a significant association. The result of chi-square showed that there wassignificant relationship between exposure of deltamethirn in broilers with several management factors (P<0,1). The relative risk analysis found that the following management practices were associated with deltamethrin residue: business system (RR= 2,585), the responsibilities within farm policies (RR= 0,302), waste handling (RR= 0,396), cage type (RR= 0,579), feed storage (RR= 1,708), water channels (RR= 2,434), and harvest period (RR= 1,893). Advice given was to conduct research with a wider scope to find out the recommendations of a more comprehensive broiler management especially in reducing the risk of exposure to deltamethrin.